Praktik Pencatatan Keuangan Gereja Paroki Hati Kudus Yesus Ambon - Meiske Wenno; Agnes Soukotta; Erfendi Regar (CV. Multi Kreasi Media, 2023)
The purpose of this service is to provide knowledge to congregation treasurers and organizational service providers about the importance of financial records in managing church finances. The approach technique used is seminars and simulations or direct training. It is hoped that this service will have an impact on members of the Sacred Heart of Jesus Parish congregation, namely improving church financial management and implementing financial records to achieve transparency in financial management.